People's intuitions about intuitive insight and intuitive choice. [article]. - Inbar, Yoel
How do people balance intuition and reason when making decisions?We report 6 studies that indicate that people are cued by the features of the decision problem to follow intuition or reason when making their choice. That is, when features of the choice resemble features commonly associated with rational processing, people tend to decide on the basis of reason; when features of the choice match those associated with intuitive processing, people tend to decide on the basis of intuition. Choices that are seen as objectively evaluable (Study 1A), sequential (studies 1B and 3), complex (Study 2) or precise (Study 4) elicit a preference for choosing rationally. This framework accurately predicts people's choices in variants of both the ratio-bias (Study 3) and ambiguity-aversion paradigms (Study 4). Discussion focuses on the relationship between the task cuing account, other decision-making models, and dual-process accounts of cognition.
Keywords: Intuition; Reason; Rationality; Choice